2011
DOI: 10.1371/journal.pone.0024547
|View full text |Cite
|
Sign up to set email alerts
|

Unique Residues Involved in Activation of the Multitasking Protease/Chaperone HtrA from Chlamydia trachomatis

Abstract: DegP, a member of the HtrA family of proteins, conducts critical bacterial protein quality control by both chaperone and proteolysis activities. The regulatory mechanisms controlling these two distinct activities, however, are unknown. DegP activation is known to involve a unique mechanism of allosteric binding, conformational changes and oligomer formation. We have uncovered a novel role for the residues at the PDZ1:protease interface in oligomer formation specifically for chaperone substrates of Chlamydia tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…None of the activators could induce proteolytic activity in either the R362L or R224A mutant (Fig. 5A, B), while wild-type CtHtrA proteolysis was activated 2.7-fold in the presence of MOMP, 1.9-fold in the presence of Act1, 1.2-fold in the presence of Act2, 1.1-fold in the presence of OmpA, and 1.2-fold in the presence of PmpC, as previously observed [26]. Given the proteolytic inactivity of these mutants, we then tested whether this correlated with an oligomeric preference for inactive hexamers, but oligomerization assays showed that both mutants readily oligomerized to 24-mer in the presence of each activator (Fig.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…None of the activators could induce proteolytic activity in either the R362L or R224A mutant (Fig. 5A, B), while wild-type CtHtrA proteolysis was activated 2.7-fold in the presence of MOMP, 1.9-fold in the presence of Act1, 1.2-fold in the presence of Act2, 1.1-fold in the presence of OmpA, and 1.2-fold in the presence of PmpC, as previously observed [26]. Given the proteolytic inactivity of these mutants, we then tested whether this correlated with an oligomeric preference for inactive hexamers, but oligomerization assays showed that both mutants readily oligomerized to 24-mer in the presence of each activator (Fig.…”
Section: Resultssupporting
confidence: 86%
“…The active site residues (His143, Asp173 and Ser247) are bordered with a red box, while the residues investigated in this study via mutagenesis are bordered with a black box. CtHtrA residue numbers are according to the full-length protein sequence as deposited at the National Centre for Biotechnology Information (NCBI; accession number: YP_001653297.1) [26]. EcHtrA residue numbers are according the standard system used for all published EcHtrA crystal structures [19], which begin at residue position 27 (underlined) in the full-length EcHtrA protein sequence (NCBI accession number: BAL37467.1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations